2015
DOI: 10.1080/19490976.2014.997610
|View full text |Cite
|
Sign up to set email alerts
|

Maternal exposure to fish oil primes offspring to harbor intestinal pathobionts associated with altered immune cell balance

Abstract: Keywords: colonic inflammation, infant immunity, intestinal microbiota, maternal diets, n-6 and n-3 polyunsaturated fatty acidsOur previous studies revealed that offspring from rat dams fed fish oil (at 8% and 18% energy), developed impaired intestinal barriers sensitizing the colon to exacerbated injury later in life. To discern the mechanism, we hypothesized that in utero exposure to fish oil, rich in n-3 polyunsaturated fatty acid (PUFA), caused abnormal intestinal reparative responses to mucosal injury thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 47 publications
0
20
0
1
Order By: Relevance
“…Using a genetic model of n-3 PUFA supplementation (Fat-1), Kaliannan et al demonstrated that elevated n-3 PUFA levels enhance intestinal production and secretion of intestinal alkaline phosphatase (IAP), which induces changes in the gut bacteria composition, resulting in decreased LPS production and gut permeability and, ultimately, in reduced metabolic endotoxemia and inflammation [183]. N-3 PUFA deficiency during development (over gestation and lactation) also alters the normal trajectory of intestinal microbe establishment in the intestine of offspring, with lowered bacterial density, a decreased ratio of Firmicutes to Bacteroidetes, and a decrease in several other dominant microbes [184]. These data suggest that n-3 PUFA levels modulate microbiota composition and activity during development.…”
Section: Risk Factors For Neuroinflammation and Autismmentioning
confidence: 99%
“…Using a genetic model of n-3 PUFA supplementation (Fat-1), Kaliannan et al demonstrated that elevated n-3 PUFA levels enhance intestinal production and secretion of intestinal alkaline phosphatase (IAP), which induces changes in the gut bacteria composition, resulting in decreased LPS production and gut permeability and, ultimately, in reduced metabolic endotoxemia and inflammation [183]. N-3 PUFA deficiency during development (over gestation and lactation) also alters the normal trajectory of intestinal microbe establishment in the intestine of offspring, with lowered bacterial density, a decreased ratio of Firmicutes to Bacteroidetes, and a decrease in several other dominant microbes [184]. These data suggest that n-3 PUFA levels modulate microbiota composition and activity during development.…”
Section: Risk Factors For Neuroinflammation and Autismmentioning
confidence: 99%
“…The role of host diet–gene interactions is also modulated by epigenetic effects; hypothetical effects have been proposed for n -3 LCPUFAs on cell proliferation, survival, and immunity ( 291 293 ). Maternal exposure to LCPUFA is known to alter the gut microbiota in offspring; n -3 fish oil increases Bacteroidetes; other fish oil diets increase pathobionts linked to altered immunity, namely B. wadsworthia, Enterococcus faecium , and B. fragilis , and n -6 safflower oil increases Firmicutes ( 294 296 ). PUFA (i.e., n -6) exposure can also induce epigenetic protective effects (transferrable to GF mice via FMT) in young animals against DSS colitis ( 297 ).…”
Section: Long-chain Fatty Acidsmentioning
confidence: 99%
“…Because polyunsaturated FA are essential nutrients and that the infant depends exclusively either on the maternal milk or the formula for an adequate n‐6 and n‐3 FA supply, their physiological effects have been largely described. Beneficial effects of n‐3 FA on intestinal disorders have been consistent in different experimental models of intestinal inflammation although a dual role, pro/anti‐inflammatory, was recently highlighted depending on the quality and quantity of dietary fat and the location of inflammed intestine . By contrast, less is known on the impacts of milk fat‐induced changes in formula lipid droplet composition and structure on neonatal digestive physiology.…”
Section: Potential Impacts Of Fat Source and Interfacial Composition mentioning
confidence: 99%